Welsh Politics after the EU Referendum. Issue 2 (May 2017) - Osmond, John
Abstract : This paper examines the electoral and ideological contest that has taken place between Welsh Labour and Plaid Cymru in the five National Assembly elections that have been held between 1999 and 2016. Both parties have found success when they have managed to combine effective leadership with a coherent programme and a strong sense of Welsh identity. However, the Welsh vote to leave the EU in the June 2016 referendum has dealt both parties a poor hand in speaking up for Welsh interests. Can they find a common cause in working together and also with Scotland to take Wales forward in a progressive constitutional direction?